Implementation of carrier-grade quantum communication networks over 10000 km - Hao-Ze Chen; Ming-Han Li; Yu Zhou Wang; Zhen-Geng Zhao; Cheng Ye; Fei Long Li; Zhu Chen; Sheng-Long Han; Bao Tang; Ya Jun Miao; Wei Qi (npj Quantum Information)
Abstract Quantum computing poses a serious threat to classical cryptographic algorithms based on computational complexity. Quantum key distribution (QKD), utilizing the principles of quantum mechanics, enables secure key exchange and has been proven to be an essential technology to resist the threat of quantum computing. China attaches great importance to the construction of QKD network to deal with this threat. In 2020, China established an integrated space-to-ground quantum communication network, which includes 32 backbone nodes and 4 metropolitan networks. Here we introduce China’s latest progress in the deployment of QKD networks, called the China Quantum Communication Network (CN-QCN). CN-QCN is an operational, long-range, and trusted-relay-based QKD network spanning over 10,000 kilometers, incorporating 145 fiber backbone nodes, and 20 metropolitan networks, which cover 17 provinces and 80 cities. Moreover, the network has deployed 6 ground stations linked with Jinan-1 quantum microsatellite. CN-QCN has not only surpassed its predecessor in scale, but also made significant advancements in multi-type QKD hybrid networking and long-range quantum network operation and maintenance. We present the network architecture, QKD implementation, and long-term performance of CN-QCN in this paper. This work lays the foundation for widespread applications of QKD in China.